Formação de professores EaD e a relação com o uso da tecnologia: uma análise a partir de professores egressos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This research aims to identify if, and how, teachers trained in the EaD context appropriate the use of digital technologies in their teaching practice. We understand digital technologies as the techniques that allow the digitalization of information. The research is qualitative in nature and the data was collected through questionnaires and interviews. The subjects participating in the research were 22 egresses of the Mathematics Degree Course of the State University of Ponta Grossa in the modality EaD. The data were organized and analyzed by means of Discursive Textual Analysis and Cluster Analysis, from where it was possible to identify two clusters. As a theoretical reference we used the concepts of field, capital and habitus of Bourdieu and the concepts of cyberculture, cyberspace and collective intelligence of Pierre Lévy. Our results indicate that egresses appropriate and make use in teaching practice of the teaching knowledge about digital technologies built during their initial training.
Keywords: Licenciatura em Matemática; UAB; Egressos; Habitus; Mathematics Degree; UAB; Graduates; Habitus; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA